Two regions of deletion in 9p23-24 in sporadic breast cancer - An, Hanxiang; Claas, Andreas; Savelyeva, Larissa; Schwab, Manfred (Cancer research, 1999)
Allelic deletions of 9p including band 21-22 are common in various types of human carcinomas including breast cancer. Our previous cytogenetic studies had identified constitutional chromosomal changes in 9p23-24 in patients of a male-breast-cancer family and 9p23-24 alterations in a cell line established from a sporadic female breast cancer. To find out whether this genomic region is involved more frequently in alterations in sporadic breast cancers, we have surveyed 80 microdissected tumor samples for both loss of heterozygosity (LOH) and homozygous deletion at 22 microsatellite loci spanning 9p22 to 9p24 using fluorescent multiplex PCR. LOH at one or more loci was observed in 32 (40%) of these tumors. Homozygous deletion was detected in four cases. Eleven tumors had LOH at all of the informative loci analyzed, whereas 21 tumors showed partial-terminal or interstitial allelic loss of 9p. Deletion mapping identified two common regions of deletion: (a) 4 cM including D9S281 to D9S286; and (b) 1 cM including D9S1808 to D9S268.